2017
DOI: 10.1589/jpts.29.1216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endurance exercise and half-bath on body composition, cardiorespiratory system, and arterial pulse wave velocity in men with intellectual disabilities

Abstract: [Purpose] The purpose of this study was to investigate the effects of endurance exercise and half-bath on body composition, cardiorespiratory system, and arterial pulse wave velocity of men with intellectual disabilities. [Subjects and Methods] Twenty-four men with intellectual disabilities, but capable of learning, were randomly assigned to aerobic exercise (N=8), half-bath (N=8), or control (N=8) treatment groups. Over the 12-week treatment period, the aerobic exercise group did treadmill and stationary bicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 8 publications
(7 reference statements)
0
33
0
Order By: Relevance
“…An increasing number of studies have reported positive effects of different exercise programs on vascular function and structure in adults without disabilities [ 82 84 ]. On the other hand, 12 weeks of CAEP reduced arterial stiffness in young adults with ID [ 85 ]. Nevertheless, modalities of exercise training such as short intermittent-bouts of high-intensity exercise, should be further explored in adults without intellectual disabilities and, even more, in adults and seniors with ID.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have reported positive effects of different exercise programs on vascular function and structure in adults without disabilities [ 82 84 ]. On the other hand, 12 weeks of CAEP reduced arterial stiffness in young adults with ID [ 85 ]. Nevertheless, modalities of exercise training such as short intermittent-bouts of high-intensity exercise, should be further explored in adults without intellectual disabilities and, even more, in adults and seniors with ID.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen RCTs met all the inclusion criteria and were therefore included in the qualitative synthesis of this review [25][26][27][28][29][30][31][32][33][34][35][36][37] (Table 1).…”
Section: Study Selection and Qualitative Synthesismentioning
confidence: 99%
“…Weekly frequencies and training session durations tested in the studies ranged from 2 to 5 times/week (mean 3 ± 0.7), and from 30 to 70 minutes/session (mean 52.7 ± 10.9 minutes). Eight trials 26,27,30,[32][33][34][35]37 assessed the effects of aerobic exercise, three studies 25,29,31 evaluated the effects of a strength training program, other three trials 28,30,36 assessed the effects of a combined exercise training (eg, aerobic exercise plus strength training). Among the eight trials where the effects of a continuous aerobic exercise were assessed, three studies presented other arms of intervention comprising combined exercise training, 30 interval aerobic exercise, 35 and a halfbath program.…”
Section: Study Selection and Qualitative Synthesismentioning
confidence: 99%
See 2 more Smart Citations